PENGARUH PENGGUNAAN MODEL TEAM GAMES TOURNAMENT BERBANTUAN MEDIA GEOBOARD TERHADAP HASIL BELAJAR MATERI BANGUN DATAR SISWA KELAS II SD NEGERI LAMSAYUEN ACEH BESAR - Raudhaton; Intan Safiah; Linda Vitoria (STKIP Subang, 2026)
This study aimed to determine the effect of the Teams Games Tournament (TGT) learning model assisted by Geoboard media on the mathematics learning outcomes of second-grade students at SD Negeri Lamsayuen Aceh Besar on the topic of plane figures. This study employed a quantitative approach with a quasi-experimental design. The sample consisted of 36 students divided into an experimental class and a control class. Data were collected through learning outcome tests and analyzed using the Mann-Whitney U test. The results showed that the average score of the experimental class was 95.5, higher than the control class at 56.25. The hypothesis test showed a significance value of 0.000 < 0.05. It can be concluded that the TGT learning model assisted by Geoboard media had a significant effect on students’ mathematics learning outcomes.